Effect of Tool Pin Length on Microstructure and Mechanical Strength of the FSW Joints of Al 7075 Metal Sheets - Agata Wronska; Jacek Andres; Tomasz Altamer; Agata Dudek; Robert Ulewicz (Communications - Scientific letters of the University of Zilina, 2019)
The Friction stir welding (FSW) is a complex process, depending on many factors: machine, clamping device, material and tools. Parameters that have a direct impact on the quality of the joint include the rotational speed, welding speed, clamping force, geometry and tool plunging depth. The paper presents the results of experimental studies concerning the effect of tool pin length on the microstructure and mechanical strength of joints of thin sheets made of Al 7075 alloy. A tool with an adjustable pin with concave shoulder was used to weld the joints. Different pin lengths were used, which were selected with respect to the thickness of the welded joint. The specimens were subjected to visual evaluation, metallographic tests and mechanical strength testing. The results indicate that the pin length has a decisive effect on the microstructural changes in the joint and thus influencing the strength of the FSW joints.